The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/wcc.262
|View full text |Cite
|
Sign up to set email alerts
|

Communication strategies for earning trust in climate change debates

Abstract: Climate scientists need the trust of lay audiences if they are to share their knowledge. But significant audience segments—those doubtful or dismissive of climate change—distrust climate scientists. In response, climate scientists can undertake one of two general communication strategies for enhancing trust, each appealing to one of two broad types of cognitive processing mechanisms. In the first, the communicator displays traits like humor, attractiveness, vigorous delivery, and likeability that audiences use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 55 publications
5
70
0
Order By: Relevance
“…Results of this study confirm earlier research that has shown that personal trust in climate science is a key lever for climate awareness and action (Malka et al 2009;Kahan et al 2012). This highlights the importance of communication interventions to improve public trust in climate science (Goodwin and Dahlstrom 2014) to enhance awareness and knowledge about climate change impacts and adaptation options (Moser 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study confirm earlier research that has shown that personal trust in climate science is a key lever for climate awareness and action (Malka et al 2009;Kahan et al 2012). This highlights the importance of communication interventions to improve public trust in climate science (Goodwin and Dahlstrom 2014) to enhance awareness and knowledge about climate change impacts and adaptation options (Moser 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Trust is receiving growing attention as one of the central issues in science communication. Even though overall trust in science remains strong (5), many are pointing to a crisis in trust between the public and specific areas of science as an obstacle to successful science communication (73,74). For example, survey data suggest that trust in institutional actors matters more for the acceptance of technologies than individual knowledge or education levels (75,76).…”
Section: Future Narrative Intersections With Science Communicationmentioning
confidence: 99%
“…Similarly, the link between knowledge and concern about climate change was found to depend upon levels of trust in scientists (77). Although persuasion theories suggest peripheral source cues that lend themselves to trustworthiness (78), developing trust in the midst of more controversial science communication contexts demands different tactics, but still remains challenging (74).…”
Section: Future Narrative Intersections With Science Communicationmentioning
confidence: 99%
“…Goodwin and Dahlstrom [100] explored the levels of trust between climate scientists and their lay audiences, and suggested that trust was established, at least in part, when communicators make themselves vulnerable to their audiences by offering predictions that may in the end be proven wrong and by accepting the consequences of these incorrect predictions. On this premise, weather forecasters are highly trusted, not because they are flawless in their predictions, but because they make predictions on a daily basis that are then tested empirically by their lay audience.…”
Section: Climate Change Communicationmentioning
confidence: 99%